Análises ontogenéticas em sementes de euphorbiaceae - De Oliveira, Jonathas Henrique Georg; Paoli, Adelita Aparecida Sartori [UNESP] (My University, 2014)
Euphorbia cotinifolia and Jatropha gossypiifolia belong to Euphorbiaceae, and to the respective subfamilies Acalyphoideae, Euphorbioideae and Crotonoideae. Information on morphology and seminal development of Euphorbiaceae are lean in literature. This research aims to monitor the morphoanatomic development of the involved species. The ovule of these species are anatropous, sessile, bitegmic and crassinucelate. The micropyle, straight, is bounded by endostome and exostome, and obliterated by the projection of the nucellus, not very evident in A. gracilis. The seeds are considered exotégmic, albuminous endosperm at maturity containing aleurone grains. The embryo with hypocotyl-radicle axis is short, broad and foliaceous cotyledons, being distinguished later: first, all the seminal wrap development occurs, so that it evolves completely. J. gossypiifolia is endopachichalazal and presents mixed endosperm: cell nucleous. Caruncule is evident in J. gossypiifolia, but it is inconspicuous in the other two species.
Ontogenetic analyzes in seeds of Euphorbiaceae
Keywords: Anatomy; Endosperm; Integument; Morphology; Nucellus